2016
DOI: 10.1007/s00595-016-1406-5
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of tolvaptan in the perioperative management of chronic kidney disease patients undergoing open-heart surgery

Abstract: Tolvaptan can safely be used for CKD patients undergoing open-heart surgery and can provide a feasible urine volume without leading to a deterioration of their renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 34 publications
1
18
1
Order By: Relevance
“…All studies that compared the difference between patients with tolvaptan and those without described that urine output in the tolvaptan group increased significantly compared to the nontolvaptan (control) group (Table 1) [36][37][38][39][40][41][42][43][44]. This effect seemed to occur around postoperative day 1-3 (Fig.…”
Section: Efficacy Of Tolvaptan After Surgerymentioning
confidence: 99%
“…All studies that compared the difference between patients with tolvaptan and those without described that urine output in the tolvaptan group increased significantly compared to the nontolvaptan (control) group (Table 1) [36][37][38][39][40][41][42][43][44]. This effect seemed to occur around postoperative day 1-3 (Fig.…”
Section: Efficacy Of Tolvaptan After Surgerymentioning
confidence: 99%
“…The authors of that study found tolvaptan to be an effective diuretic without causing electrolyte disbalance or worsening of renal function. Other published retrospective observational studies have also reported similar results (7)(8)(9). However, a significant limitation of observational studies is the high risk of bias.…”
Section: Efficacy Of Tolvaptan For Fluid Management After Cardiovascumentioning
confidence: 53%
“…Five were excluded as they were not RCTs ( 1 , 7 , 9 , 13 , 14 ). One study was conducted on pediatric patients ( 15 ), and another on patients with chronic kidney disease ( 8 ). Finally, four studies were included in this systematic review and meta-analysis ( 2 , 16-18 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Little is known about the impact of tolvaptan in CKD patients in the perioperative management of open-heart surgery. 9) In the present study, the purpose was to retrospectively assess the efficacy of tolvaptan administration in CKD patients in the early postoperative period, following open-heart surgery.…”
Section: Introductionmentioning
confidence: 99%